Bimbingan Ibadah Di Panti Asuhan Muhammadiyah Cabang Guguak Ii Kabupaten 50 Kota - Hamidah Ali; Iswantir Iswantir; Charles Charles; Arifmiboy Arifmiboy (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research is motivated by the phenomena that occur in orphanages where the ability of foster children to understand religion is considered to be lacking because of insight and knowledge and lack of attention, affection from parents, lack of facilities and infrastructure in religious guidance activities and religious guidance activities at orphanages. Muhammadiyah Aisyiah is not optimal. To answer this statement, this researcher uses a qualitative descriptive approach with a field research study design. In this study, researchers used observation and interview methods as a means of collecting data from primary and secondary data sources.The conclusions that can be drawn from this study are (1) that the results of the worship guidance activities at the orphanage are quite good, because now the children have started to understand what is being taught and immediately apply it in their daily lives. (2) Supporting and inhibiting factors in the implementation of religious guidance. The supporting factors are: the willingness of foster children is quite high, and the existence of an orphanage prayer room that supports the implementation of religious guidance. While the inhibiting factors for religious guidance activities are the lack of supporting facilities for study rooms, lack of funds to support religious guidance activities, lack of time for prayer guidance activities and a lack of teaching staff.